2005
DOI: 10.1002/glia.20297
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the stress‐associated gene p8 in mouse models of demyelination and in multiple sclerosis tissues

Abstract: Cuprizone-induced demyelination is a mouse model of multiple sclerosis (MS) as cuprizone-fed mice exhibit neuroin-flammation and demyelination in the brain. Upon removal of cuprizone from the diet, inflammation is resolved and reparative remyelination occurs. In an Affymetrix Gene-Chip analysis, the stress-associated gene p8 was strongly upregulated (>10×) during cuprizone-induced demyelination but not remyelination. We verified this upregulation (>15×) of p8 in the CNS during demyelination by real-time polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
(36 reference statements)
1
15
0
Order By: Relevance
“…3A, TCR-b and Th1-cytokine (IFN-g, Lymphotoxin-a) transcript levels were increased in CNS from Ovx mice that developed significantly worse EAE than sham-operated controls. Likewise, we found that mRNA of various chemokines (TCA-3, MCP-1, C10, RANTES, MIG, MDC) known to be early upregulated in the CNS from mice developing EAE [18] and expression of the stress-associated gene P8, which is linked with active demyelination [19], were higher in Ovx mice relative to shamoperated control (Supporting Information Fig. 5A and B).…”
Section: Resultsmentioning
confidence: 69%
“…3A, TCR-b and Th1-cytokine (IFN-g, Lymphotoxin-a) transcript levels were increased in CNS from Ovx mice that developed significantly worse EAE than sham-operated controls. Likewise, we found that mRNA of various chemokines (TCA-3, MCP-1, C10, RANTES, MIG, MDC) known to be early upregulated in the CNS from mice developing EAE [18] and expression of the stress-associated gene P8, which is linked with active demyelination [19], were higher in Ovx mice relative to shamoperated control (Supporting Information Fig. 5A and B).…”
Section: Resultsmentioning
confidence: 69%
“…Induction of p8 mRNA is rapid, strong, and transient in response to divergent stresses such as systemic LPS or CCl 4 (13,14), demyelination-inducing agents (15), serum withdrawal (2), and chemical inducers of cell cycle arrest (16). p8 is also induced in response to TGF␤ (7), TNF␣ (10,17), glucose (18), cannabinoids (12), 1,25-dihydroxyvitamin D 3 (19), angiotensin, and ET (20) ( Table 1).…”
Section: P8 Structure and Expressionmentioning
confidence: 99%
“…The stress-associated gene P8 is a newly identified marker that is associated with active demyelination (35). We used realtime PCR to quantitate P8 gene expression in the spinal cords of Astro CD24TG mice and NTG mice on day 20 (peak of disease) and day 40 (EAE recovery) after immunization.…”
Section: Neurogenesis and Remyelination Levels Are Similar In Cd24 Trmentioning
confidence: 99%